Self-referral practice and associated factors among women who gave birth in South Gondar zone primary hospitals, Northwest Ethiopia: a cross-sectional study design - Eshetie, Ayenew; Belachew, Tadele Biresaw; Negash, Wubshet Debebe; Asmamaw, Desale Bihonegn; Muktar, Sualiha Abdulkader; Kebede, Adane (Frontiers in Public Health, 2023)
Background Patient self-referral is when patients refer themselves to upper-level health facilities without having to see anyone else first or without being told to refer themselves by another health professional. Self-referral leads to a diminished quality of healthcare services. However, globally, many women who gave birth referred themselves to hospitals without having referral sheets, including in Ethiopia and the study area. Therefore, this study aimed to assess self-referral practice and associated factors among women who gave birth in South Gondar zone primary hospitals in Northwest Ethiopia. Methods A cross-sectional mixed-method study was conducted among women who gave birth in South Gondar zone primary hospitals between 1 June 2022 and 15 July 2022. Semi-structured questionnaires were used to gather quantitative data from 561 participants who were selected by a systematic random sampling technique. Interview guides were used to collect qualitative data from selected six key informants. Quantitative data were entered into Epi Data version 4.6.0.4 and then exported to the statistical software SPSS version 25 for further analysis. Thematic analysis using open code version 4.02 software was applied for qualitative data analysis. A binary logistic regression analysis was employed. In a bivariable analysis, a p < 0.25 was used to select candidate variables for multivariable analysis. P < 0.05 and a 95% confidence interval were used to determine significant variables on the outcome of interest. Results The overall magnitude of self-referral was 45.6%, with 95% CI (41.5%, 49.9%). They had no antenatal care (ANC) follow-up (AOR = 3.02, 95% CI: 1.64–5.57) and 1–3 ANC follow-ups (AOR = 1.57, 95% CI: 1.03–2.41), poor knowledge about the referral system (AOR = 4.04, 95% CI: 2.30–7.09), and use of public transportation (AOR = 2.34, 95% CI: 1.43–3.82), which were significantly associated with self-referral practice. Conclusion This study showed that nearly half of the deliveries were self-referred. ANC follow-up, women's knowledge of the referral system, and mode of transportation were factors significantly associated with the self-referral practice. Therefore, developing awareness-creation strategies and increasing coverage of ANC 4 and above are necessary interventions to reduce the self-referral practice.